2017
DOI: 10.1002/ijc.31030
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptor GPR55 promotes colorectal cancer and has opposing effects to cannabinoid receptor 1

Abstract: The putative cannabinoid receptor GPR55 has been shown to play a tumor-promoting role in various cancers, and is involved in many physiological and pathological processes of the gastrointestinal (GI) tract. While the cannabinoid receptor 1 (CB 1 ) has been reported to suppress intestinal tumor growth, the role of GPR55 in the development of GI cancers is unclear. We, therefore, aimed at elucidating the role of GPR55 in colorectal cancer (CRC), the third most common cancer worldwide. Using azoxymethane (AOM)-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 47 publications
2
72
0
Order By: Relevance
“…Since we had recently found that GPR55-deficient mice had a significantly lower tumor burden in various models of colorectal cancer [13], we investigated whether these effects were mediated by the epithelial cells. Therefore, we analyzed six commercially available colon cancer cell lines for their GPR55 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since we had recently found that GPR55-deficient mice had a significantly lower tumor burden in various models of colorectal cancer [13], we investigated whether these effects were mediated by the epithelial cells. Therefore, we analyzed six commercially available colon cancer cell lines for their GPR55 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The transfection was performed with Lipofectamine 2000 according to the manufacturer’s protocol. Transfected cells were selected with 4 mg/mL G418 (Life Technologies) 48 h after transfection, grown to confluence, and subsequently sorted on a FACSAria (BD Biosciences, Franklin Lakes, NJ, USA) as described previously [13]. Sorted cells were maintained as HCT116-GPR55 (HCT55) and SW480-GPR55 (SW55) in their respective media, which were supplemented with 0.5 mg/mL G418.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unknown whether these changes actually correlate with the disease progress. With regard to CRC, in vitro data from colon cancer cell lines convincingly show antiproliferative effects of cannabinoids [19] and, in fact, models of CRC in knockout mice suggest an anti-oncogenic role for at least CB 1 [20,21]. With regard to CB 2 , however, studies in human CRC patients show that its expression correlates with a decreased survival [22].…”
Section: Introductionmentioning
confidence: 99%